Las políticas públicas y su incidencia en el presupuesto de las universidades públicas de Manabí en el periodo 2020 - Espinoza Calle, Arleth Alejandra (2023)
The present investigation had as essential objective to analyze the incidence of public policies in the budget of the public universities of Manabí for its operation; For this reason, public policies, criteria and quality standards in higher education, responsible autonomy, self-management, budget allocation criteria, budget execution, etc. are discussed. The research had a qualitative approach; the analytical, descriptive, and explanatory method was applied; due to the design or form of information collection, the investigation was documentary; Field research was implemented through the application of the interview technique and the questionnaire as an instrument. The investigation procedure was developed in three phases: description of the public policies applied in the budget allocation of the universities, analysis of the characteristics, limitations, and nature of the public policies in the granting of economic resources for the universities of Manabí and Proposal of an information plan with new strategies to improve the management of the different budget items in the universities of Manabí. Finally, it was concluded that: public policies have improved the quality standards of Higher Education Institutions in the country; However, the resources assigned to universities limit budget execution due to recurring cuts and greatly limit the normal functioning of Higher Education Institutions.